A TEACHING PRACTICE INCORPORATING STUDENTS’ GOAL AND INSTITUTIONAL GOAL IN BIG-SIZED ENGLISH CLASSES - Ari Nurweni (Universitas Negeri Padang, 2017)
This paper reports a teaching and learning practice in three big-sized English classes incorporating the learning goal set by the students and that by their institution, and three questions in relation to the teaching and learning practice were investigated: 1) What do the students perceive at a text-based teaching and learning?; 2) What problems do the students face at a text-based teaching and learning class?; and 3) What do the students learn at the text-based teaching and learning ?The subjects of this study were 208 first year students of a state engineering institute in Lampung, Sumatera, Indonesia, who were put in 3 different classes. The teaching and learning activities were based on academic texts selected by the students in a group of ten. In every meeting a group of the students who had prepared a two-page English academic text presented its title and key words to the class, whereas the other groups asked questions based on the title and key words which had to be answered by the group orally. In every meeting at the end of the class the students were asked to write a journal according to the research questions. The results showed that they perceived the teaching practice differently, they had some problems,but they learnt some linguistic elements as well as skills, and they realized that they still needed to improve their English skill and to improve their participation in speaking.